2022
DOI: 10.1128/jcm.00600-22
|View full text |Cite
|
Sign up to set email alerts
|

Partial ORF1ab Gene Target Failure with Omicron BA.2.12.1

Abstract: Mutations in the genome of SARS-CoV-2 can affect the performance of molecular diagnostic assays. In some cases, such as S-gene target failure, the impact can serve as a unique indicator of a particular SARS-CoV-2 variant and provide a method for rapid detection.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…In March 2021, the FDA reported that SARS-CoV-2 with an N gene point mutation may cause N gene target failure (NGTF) for the 1st-generation Xpress tests ( 1 ). This communication from the FDA reinforced multiple published reports of NGTF from laboratories throughout the United States ( 2 11 ). In the future, there may be the potential for the FDA to encourage the public availability of commercial primer and probe sequences to assist laboratories in monitoring circulating variants and their performance in test methods; however, if the disclosures are not mandated by the FDA for all commercial assays, it would be difficult to encourage competitive commercial entities to release proprietary information.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In March 2021, the FDA reported that SARS-CoV-2 with an N gene point mutation may cause N gene target failure (NGTF) for the 1st-generation Xpress tests ( 1 ). This communication from the FDA reinforced multiple published reports of NGTF from laboratories throughout the United States ( 2 11 ). In the future, there may be the potential for the FDA to encourage the public availability of commercial primer and probe sequences to assist laboratories in monitoring circulating variants and their performance in test methods; however, if the disclosures are not mandated by the FDA for all commercial assays, it would be difficult to encourage competitive commercial entities to release proprietary information.…”
Section: Discussionsupporting
confidence: 62%
“…These mutations and polymorphisms can impact the infectiousness and immunogenicity of the virus, but the changes can also impact the performance of IVDs. Mutations can yield reduced sensitivity or complete failure in the detection of genomic regions that are targets of nucleic acid amplification tests (NAATs) ( 2 11 ). Most IVD NAATs used to detect SARS-CoV-2 contain redundancy, so if one target fails due to a viral genomic mutation, the qualitative detection of the virus remains intact ( 7 ), but some variants have mutations that can cause complete diagnostic failure ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The D614G mutation, found in VoCs since early 2020, may be involved in Spike stability, viral replication, and Spike conformation shifting, thus improving viral infectivity and transmissibility ( Hou et al., 2020 ; Korber et al., 2020 ; Yurkovetskiy et al., 2020 ). As a key mutation in BA.2.12.1 strains ( Rodino et al., 2022 ), S704L is another high-scoring mutation that has contributed positively across all three perspectives by computational methods of validations, indicative of its possibly compound effects, although it has not been extensively studied by scholars. Overall, most of the top twenty mutations identified in this research can possess at least one validated positive effect on viral fitness, demonstrating the effectiveness of our estimation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the impact of genomic changes on assay performance cannot be predicted locally and relies heavily on prompt notification by the manufacturers. Such notification does not always occur, and often the first sign that an assay is impacted is observed by the astute clinical microbiologist, as shown recently ( 10 ). Amplifying this communication system for all assays more systematically for the many tests used by laboratories would benefit all laboratories using commercial tests.…”
Section: Connecting Laboratory and Clinical Data For Patient And Diag...mentioning
confidence: 97%